Strategic Water - Lorenz, Frederick; Erickson, Edward J. (Marine Corps University Press (MCUP), 2023)
The issue of freshwater scarcity has always been of vital concern to humans, and today it is increasingly characterized as a strategic factor in security planning. In the Euphrates-Tigris basin, water apportionment and management combined with climate change are increasingly emerging as threats to regional stability. The United States has a longterm strategic interest in the Euphrates-Tigris basin that, in turn, is directly linked to the national interests of the riparian states. The expanded second edition of Strategic Water: Iraq and Security Planning in the Euphrates-Tigris Basin updates analysis of the geopolitical situation and expands coverage of the aspirations of the basin countries. Finally, the book presents new conclusions and a proposed framework for action in the next 10 to 20 years.